2018
DOI: 10.1007/s13280-018-1115-y
|View full text |Cite
|
Sign up to set email alerts
|

Global challenges for seagrass conservation

Abstract: Seagrasses, flowering marine plants that form underwater meadows, play a significant global role in supporting food security, mitigating climate change and supporting biodiversity. Although progress is being made to conserve seagrass meadows in select areas, most meadows remain under significant pressure resulting in a decline in meadow condition and loss of function. Effective management strategies need to be implemented to reverse seagrass loss and enhance their fundamental role in coastal ocean habitats. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
149
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(178 citation statements)
references
References 77 publications
(107 reference statements)
0
149
0
1
Order By: Relevance
“…Table 1 in Garcias-Bonet and . Provided estimates of their global extent of seagrass meadows ranging from a documented 326 000 km 2 (Unsworth et al, 2019) to a predicted 1.6 × 10 6 km 2 (Jayathilake and Costello, 2018), seagrass meadows may be important yet hitherto overlooked contributors to CH 4 emissions. Garcias-Bonet and reported that seagrasses could contribute to global CH 4 emissions by releasing CH 4 at a rate of 0.09 to 2.7 Tg yr −1 , which may increase the contribution of marine global emissions to previously reported global estimates by about 30 % (Garcias-Bonet and .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 in Garcias-Bonet and . Provided estimates of their global extent of seagrass meadows ranging from a documented 326 000 km 2 (Unsworth et al, 2019) to a predicted 1.6 × 10 6 km 2 (Jayathilake and Costello, 2018), seagrass meadows may be important yet hitherto overlooked contributors to CH 4 emissions. Garcias-Bonet and reported that seagrasses could contribute to global CH 4 emissions by releasing CH 4 at a rate of 0.09 to 2.7 Tg yr −1 , which may increase the contribution of marine global emissions to previously reported global estimates by about 30 % (Garcias-Bonet and .…”
Section: Introductionmentioning
confidence: 99%
“…), and a greater understanding of how seagrasses provide these services is required to manage impacts on seagrass (Unsworth et al. ). In the Great Barrier Reef World Heritage Area (GBRWHA), seagrass is a key habitat supporting the outstanding universal values that led to its World Heritage status and is a critical habitat supporting fisheries production (Coles et al.…”
Section: Introductionmentioning
confidence: 99%
“…Seagrass systems have been recognized as an important resource with its functions listed by [2] [3] [4] [5]. Similar to other marine ecosystems, seagrass meadows have diminished their coverage in part driven by warming sea surface temperatures but also by the direct effect of human intervention [6]. The most obvious anthropogenic-driven impacts on seagrasses occur in coastal areas adjacent to human settlements, where physical disturbance, organic enrichment, and overfishing activities result in the greatest negative impacts [7].…”
Section: Introductionmentioning
confidence: 99%